Complete chloroplast genome sequence of Homalium hainanense (Salicaceae). Issue 3 (2nd July 2020) - Liu, Xiaojin; Xu, Daping; Zhang, Ningnan; Hong, Zhou
Abstract: Homalium hainanense is a large evergreen tree species belonging to Salicaceae family, and its wood is tough, fine-grained, which makes it a good source of commercial use for building construction and furniture manufacturing. In this study, we sequenced the complete chloroplast genome of H. hainanense based on next generation sequencing and used these data to assess genomic resources. The size of the H. hainanense chloroplast genome was 157, 852 bp, including a large single-copy region (85, 888 bp), a small single-copy region (16, 592 bp), and a pair of inverted repeats regions (27, 686 bp). The overall GC content of the H. hainanense chloroplast genome was 36.6%. The plastome of H. hainanense was predicted to contain 112 unique genes, including 78 protein coding genes, 30 tRNA genes and 4 rRNA genes. The reconstructed phylogeny revealed that Homalium was monophyletic and H. hainanense was sister to H. stenophyllum, H. paniculiflorum and H. racemosum.